Carbon dioxide partial pressures and emissions of the Yarlung Tsangpo River on the Tibetan Plateau - Bao, Yufei; Hu, Mingming; Li, Shanze; Wang, Yuchun; Wen, Jie; Wu, Xinghua; Sun, Meng; Du, Pengcheng (Frontiers in Environmental Science, 2023)
Rivers are important routes for material and energy transport between terrestrial and marine ecosystems. Recent global-scale assessments of carbon (C) have suggested that C emission fluxes to the atmosphere are comparable to the fluvial C fluxes to the ocean. However, many previous studies only collected data from inland rivers in low altitude regions. Therefore, it remains unclear how plateau rivers affect C flux. In this study, 20 monitoring sites were set up along the Yarlung Tsangpo (YT) River on the Tibetan Plateau and detailed observations were carried out in the wet and dry seasons. The riverine CO2 fluxes exhibited significant seasonal patterns which ranged from 597.12 ± 292.63 μatm in the wet season to 368.72 ± 123.50 μatm in the dry season. The CO2 emission flux (FCO2) obtained from floating chamber method, ranging from 8.44 ± 6.94 mmol m−2 d−1 in sunmmer to 3.62 ± 6.32 mmol m−2 d−1 in winter, with an average value of 6.03 mmol m−2 d−1. Generally, the river was a weak carbon source with respect to the atmosphere. However, the pCO2 and FCO2 were much lower than that for other large rivers around the globe, which were obviously restrained by the weak microbial activities due to the low primary productivity and carbonate buffer activities in the carbonate background. Carbon loss via atmosphere exchange in the YT River on the plateau accounted for 2.2% and 10.6% of the riverine dissolved carbon fluxes (67.77 × 109 mol a−1) according to the floating chamber and thin boundary layer methods, respectively. The YT River probably acts as a “pipeline” to transport weathered nutrients from the plateau to downstream areas. Our results demonstrated the characteristics of a “weak outgassing effect and a high transport flux of carbon” for the plateau river, which is different from rivers on plains. Considering the global relevance of Tibetan Plateau, further studies with enhanced spatiotemporal resolution are needed to better understand the important role of plateau rivers on carbon budgets and climate change over both regional and global cycles.